2016
DOI: 10.1037/per0000199
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in BPD research as indicative of a broader sea-change in psychiatric nosology.

Abstract: The aim of the Special Section that this paper contributes to is to review current trends in borderline personality disorder (BPD) research. Three major trends were identified. First, there has been a marked increase in studies that attempt to locate BPD in the dimensional latent structure of psychopathology. Second, identifying the endophenotypic markers associated with BPD has become a focus of interest. Here, we focus on one endophenotype in the form of impaired self-other processing. Third, there has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 111 publications
0
19
0
Order By: Relevance
“…This research points out that BPD typically first manifests itself in adolescence, and that adolescent BPD symptoms can be distinguished reliably from normative adolescent development [ 17 ]. Moreover, adolescence can be considered a particular sensitive period for BPD pathology to emerge [ 7 •]. Two large longitudinal studies into the trajectory of BPD from childhood into young adulthood have shown that BPD pathology has its onset in the beginning of adolescence [ 18 , 19 ].…”
Section: Waxing and Waning Course Of Bpd From Childhood To Old Agementioning
confidence: 99%
See 3 more Smart Citations
“…This research points out that BPD typically first manifests itself in adolescence, and that adolescent BPD symptoms can be distinguished reliably from normative adolescent development [ 17 ]. Moreover, adolescence can be considered a particular sensitive period for BPD pathology to emerge [ 7 •]. Two large longitudinal studies into the trajectory of BPD from childhood into young adulthood have shown that BPD pathology has its onset in the beginning of adolescence [ 18 , 19 ].…”
Section: Waxing and Waning Course Of Bpd From Childhood To Old Agementioning
confidence: 99%
“…These risk factors predict not only BPD, but a wide range of mental disorders. Prognostic factors that are specifically associated with a BPD development in children have not yet been identified [ 7 •, 21 ].…”
Section: Waxing and Waning Course Of Bpd From Childhood To Old Agementioning
confidence: 99%
See 2 more Smart Citations
“…Interpersonal problems have been suggested as the most characteristic and discriminative feature of the disorder (Fossati et al, 1999;Gunderson, 2007;Johansen, Karterud, Pedersen, Gude, & Falkum, 2004). Moreover, other cardinal symptoms of BPD, such as anger, affective instability, suicidal behavior, and impulsiveness, mainly manifest within interpersonal contexts (Sharp, 2016). Evidence has shown that interpersonal problems underlie subjective burden and behavioral deviations (e.g., self-harm and violence), and that they are related to neurobiological alterations (King-Casas et al, 2008;Lis & Bohus, 2013;Stepp, Smith, Morse, Hallquist, & Pilkonis, 2012).…”
mentioning
confidence: 99%